2021
DOI: 10.1007/s40544-021-0489-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic friction energy dissipation and enhanced contrast in high frequency bimodal atomic force microscopy

Abstract: Dynamic friction occurs not only between two contact objects sliding against each other, but also between two relative sliding surfaces several nanometres apart. Many emerging micro- and nano-mechanical systems that promise new applications in sensors or information technology may suffer or benefit from noncontact friction. Herein we demonstrate the distance-dependent friction energy dissipation between the tip and the heterogeneous polymers by the bimodal atomic force microscopy (AFM) method driving the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…The maximum energy barrier of 1T′-MoTe 2 is 53.80 meV, which is more than twice as large as that of 2H-MoTe 2 (22.20 meV). Therefore, in a random sliding process, the maxmium potential barrier that 2H-MoTe 2 needed to overcome was smaller than that of 1T′-MoTe 2 , implying less energy dissipation and smaller friction force [36]. For the case of a specific friction path, the process of sliding along the minimum energy path (MEP) was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum energy barrier of 1T′-MoTe 2 is 53.80 meV, which is more than twice as large as that of 2H-MoTe 2 (22.20 meV). Therefore, in a random sliding process, the maxmium potential barrier that 2H-MoTe 2 needed to overcome was smaller than that of 1T′-MoTe 2 , implying less energy dissipation and smaller friction force [36]. For the case of a specific friction path, the process of sliding along the minimum energy path (MEP) was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…We remark that the bottom-effect corrections are essential to provide accurate quantitative elastic property values of materials, specifically of ultrathin materials. However, many bimodal AFM applications aim to enhance the spatial resolution or material contrast. Those applications do not require any bottom-effect correction.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a series of micro-and nanoscale friction experiments have also verified the vibration-based friction phonon dissipation [36][37][38][39][40][41]. Filleter et al [42] found that the friction of monolayer graphene on SiC was larger than that of the bilayer graphene (Fig.…”
Section: Phonon Dissipationmentioning
confidence: 92%